AKT and AMPK Activation after High-Fat and High-Glucose In Vitro Treatment of Prostate Epithelial Cells - Ribeiro, D. L.; Goes, R. M. [UNESP]; Pinto-Fochi, M. E. [UNESP]; Taboga, S. R. [UNESP]; Abrahamsson, P. -A.; Dizeyi, N. (Georg Thieme Verlag Kg, 2014)
Considering the increasing consumption of saturated fat and glucose in diets worldwide and its possible association to carcinogenesis, this investigation analysed the proliferation profile of nonmalignant human prostate epithelial cells after exposure to elevated levels of fat and glucose. PNT1A cells were cultured with palmitate (100 or 200 mu M) and/or glucose (450mg/dl) for 24 or 48 h. Treated cells were evaluated for viability test and cell proliferation (MTS assay). AKT and AMPK phosphorylation status were analysed by Western blotting. After 24 h of high-fat alone or associated with high-glucose treatment, there was an increase in AMPK and AKT activation associated to unchanged MTS-cell proliferation. Following 48 h of high-fat but not high-glucose alone, cells decreased AMPK activation and maintained elevated AKT levels. These data were associated to increased cell proliferation after further high-fat treatment. After longer high-fat exposure, MTS revealed that cells remained proliferating. High-glucose alone or associated to high-fat treatment was not able to increase cell proliferation and AKT activation. A high-fat medium containing 100 mu M of palmitate stimulates proliferation in PNT1A cells by decreasing the activation of AMPK and increasing activation of AKT after longer exposure time. These findings improve the knowledge about the negative effect of high levels of this saturated fatty acid on proliferative disorders of prostate.
Keywords: prostate; palmitate; glucose; cell proliferation; AMPK; AKT